Root System Response and Yield of Irrigated Rice in Relation to Irrigation, Potassium and Nitrogen under Subtropical Conditions - Md. Salahuddin Kaysar; Uttam Kumer Sarker; Sinthia Afsana Kheya; Ahmed Khairul Hasan; Md. Alamgir Hossain; Uzzal Somaddar; Gopal Saha; Apurbo Kumar Chaki; Abeer Hashem; Elsayed Fathi Abd_Allah; Md. Romij Uddin (Agronomy, 2023)
Irrigation and fertilizer are two essential factors affecting rice root traits and yield. In this respect, a pot experiment was performed at the boro (dry season irrigated) season of 2021–2022 in the Department of Agronomy of Bangladesh Agricultural University, Mymensingh, Bangladesh. The variety Binadhan-10 was planted at two irrigation conditions, i.e., saturation (S) and continuous flooding (CF); two potassium (K) doses, e.g., 65 kg ha−1 (K65) and 98 kg ha−1 (K98); and two nitrogen (N) doses, i.e., 140 kg ha−1 (N140) and 210 kg ha−1 (N210). The experiment was laid in a split plot design with eight treatments and replicated thrice. The findings confirmed the significant variation in irrigation, K and N and the effects on root number (RN), root length (RL), root volume (RV), leaf area index (LAI), total dry matter (TDM), yield attributes and yield. Considering the interaction among irrigation, K and N, the S conditions with K65 and N140 showed best performance in relation to root parameters. At 80 DAT, the highest RN (373.00), RL (1700.00 cm), RV (8.90 cm3 hill−1), LAI (4.94) and TDM (25.83 g plant−1) was obtained from this combination. Grain yield (GY) and root traits, except root porosity, showed a significant positive association. Grain yield (GY) was the highest (27.12 g pot−1) under S conditions with K65 and N140. Therefore, the variety Binadhan-10 can be successfully cultivated with K65 and N140 under S conditions.